KAJIAN SISTEM DRAINASE LAPANGAN SEPAK BOLA STADION MINI UNIVERSITAS ISLAM RIAU - Yolly Adriati (Universitas Teuku Umar, 2017)
Stadium football field at the Islamic University of Riau Mini faced with the problem of water puddle when it rains due to the absence of drainage systems. Soccer field drainage plan aims to resolve the issue. UIR planned soccer field is equipped with an athletic track. Drainage system is planned to use drainage pipes with holes that are placed below the pore surface of the field. Soil structure on the soccer field is planned to use 3 pieces of layers, the layer of soil and manure, a layer of fine sand, and gravel layers with each layer thickness of 10 cm. From the analysis concluded that in order to drain the water due to rain at the Mini Stadium football field Riau Islamic University used 54 kinds of PVC drainage pipe Ø 4